2016
DOI: 10.1177/1748895816669214
|View full text |Cite
|
Sign up to set email alerts
|

Sociological stalking? Methods, ethics and power in longitudinal criminological research

Abstract: Scholarship on criminal careers and desistance from crime employing longitudinal methodologies has paid scant attention to sociological and anthropological debates regarding epistemology, reflexivity and researcher positionality. This is surprising in light of a recent phenomenological turn in desistance research wherein (former) lawbreakersÕ identity, reflexivity, and self-understanding have become central preoccupations. In this article I interrogate aspects of the methodological ÔundersideÕ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Due to this, criminally active women exposed to violence typically only contact hospitals and authorities in an emergency [22,28]. Contacting authorities while in a drug (ab)using and criminal lifestyle can also lead to other repercussions such as a risk of losing care of children ( [28]; see also [60]). This is likely to be especially true in Sweden (where the present study was conducted) since Sweden has a history of punitive social policy on drug use, and even the personal intake of illicit drugs is criminalized [21].…”
Section: Violence Against Women In Criminal Lifestylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this, criminally active women exposed to violence typically only contact hospitals and authorities in an emergency [22,28]. Contacting authorities while in a drug (ab)using and criminal lifestyle can also lead to other repercussions such as a risk of losing care of children ( [28]; see also [60]). This is likely to be especially true in Sweden (where the present study was conducted) since Sweden has a history of punitive social policy on drug use, and even the personal intake of illicit drugs is criminalized [21].…”
Section: Violence Against Women In Criminal Lifestylesmentioning
confidence: 99%
“…As shown by previous research, isolation is a common feature of intimate partner violence. Research has also shown that the stigma of being perceived as a convicted woman may lead to isolation due to shame [28,58,60,65]. This, in combination with the strong link between violent victimization and mental illnesses such as PTSD, could make it harder for a willing desister to (re)establish contact with conventional society.…”
Section: Possible Implications Of Violent Victimization On Desistancementioning
confidence: 99%
“…Carlen and Ayres França, 2017; hooks, 1990; Miller, 2012; Ramazanoglu and Holland, 2002; Tyler, 2008) and explorations of ‘vulnerability’, privilege and experience on the part of both the researcher and the researched (e.g. Armstrong et al, 2014; Behar, 2014 (1996); Beyens et al, 2013; Gelsthorpe, 2007; Holland, 2007; Sharpe, 2016). Scholars have explored the politics of method – how politics shape the questions we ask and how we ask them, the relationships between social science, values and ethics, and what it means to ‘do justice’ to research findings and ‘have impact’ in and with the world (e.g.…”
Section: Problems Of Power Purpose Positioning and Personhood In Rementioning
confidence: 99%
“…Reflexivity is of paramount importance in qualitative research (Armstrong et al, 2017; Sharpe, 2017), namely scrutinizing researchers’ positionality and reflecting on its effect throughout the research process, and considering the possible contradictions from wanting to ‘give a voice’ (Phillips and Earle, 2010: 372). Like interviews or observations, scholars who draw on prisoners’ letters become a research instrument (Liebling, 1999) that shapes the production and dissemination of knowledge, and that ultimately needs to be taken seriously.…”
Section: Ethics and Emotionsmentioning
confidence: 99%